(3Ydd GdMOjK heYQaI GdQLGds - (3CHh GdMSf Ydj Hf YHO Gddg Hf LYaQ Hf fLjM GdSYOi GdeOjfi,J (B234 (3g` s ((3CHh HcQ Hf Ydi Hf ESeGYjd GdCfUGQi GdHgfSi GdTGaYi s)
(3ChdgG (B:s
(3bGd (B: (3CNHQfG GdTjNGf GdEeGe GdMGaX CHh WGgQ GdSGdai s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B303s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B109 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs